Photocatalytic Degradation of Batik Cual Wastewater Using Fe3O4/SiO2/TiO2 Composite Derived From Tin Tailing - Fabiani, Verry Andre; Putri, Restani Eka; Davina, Lyra; Virliana, Zelfia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Abstract: Batik cual dye wastewater is produced from the batik cual industry in Bangka, which contains Remazol dye, which is carcinogenic and a non-biodegradable organic compound that can be a pollutant for the environment. The elevated levels of remazol dyes in Batik Cual wastewater necessitate effective and environmentally safe waste management methods. One such method is photodegradation, utilizing a Fe3O4/SiO2/TiO2 composite photocatalyst derived from tin tailings sand. The Fe3O4/SiO2/TiO2 composites were synthesized via the hetero-agglomeration method. XRF characterization revealed that the SiO2 content, following purification with HNO3 acid leaching, reached 78.63%. XRD characterization of the tin tailings indicated the presence of peaks corresponding to quartz silica. Phase analysis using XRD diffractograms for the Fe3O4/SiO2/TiO2 composites showed peaks of magnetite, quartz silica, and a predominant anatase TiO2 phase with strong diffraction patterns at 2θ angles of 27.42°; 39.19°; 44.00°, and 54.29°. UV-DRS analysis determined the band-gap energy of the Fe3O4/SiO2/TiO2 photocatalyst to be 1.9 eV. Morphological SEM analysis indicated that the synthesized Fe3O4/SiO2/TiO2 composite had a spherical, uneven, rough, and porous surface. The photodegradation of the Fe3O4/SiO2/TiO2 composite on cual batik dye waste showed that the optimal contact time for photodegradation was 60 minutes, and the catalyst dose was 500 mg at 98.1%. Consequently, these findings confirm that the Fe3O4/SiO2/TiO2 composite is a viable photocatalyst for photodegradation in handling cual batik dye waste.Abstrak: Limbah zat warna batik cual dihasilkan dari industri batik cual di Bangka yang mengandung zat warna Remazol, bersifat karsinogenik dan merupakan senyawa organik non-biodegradable yang dapat menjadi pencemar bagi lingkungan Tingginya kadar zat warna remazol pada limbah batik cual membutuhkan penanganan limbah yang tepat dan aman bagi lingkungan. Salah satu metode yang dinilai efektif yaitu metode fotodegradasi menggunakan fotokatalis komposit Fe3O4/SiO2/TiO2berbahan pasir tailing timah. Karakterisasi XRF menunjukkan kadar SiO2 setelah dilakukan pemurnian acid leaching HNO3 mencapai 78,63%. Hasil karakterisasi XRD tailing timah menunjukkan terdapatnya puncak yang menandakan silika kuarsa. Komposit Fe3O4/SiO2/TiO2berdasarkan analisis fasa menggunakan XRD difraktogram menunjukkan puncak magnetit, silika kuarsa dan didominasi fasa TiO2 anatase pada sudut 2θ 27,42°; 39,19°; 44,00°; dan 54,29. Berdasarkan analisis UV-DRS didapatkan energi ban-gap untuk fotokatalis Fe3O4/SiO2/TiO2sebesar 1,9 eV. Analisis morfologi pada komposit Fe3O4/SiO2/TiO2 menunjukkan bentuk sperik, permukaan yang tidak rata, kasar dan berpori. Uji fotodegradasi komposit Fe3O4/SiO2/TiO2terhadap limbah zat warna batik cual didapatkan waktu kontak optimal fotodegradasi pada waktu 60 menit dan massa komposit 500 mg sebesar 98.1%. Sehingga dengan hasil tersebut dapat disimpulkan bahwa komposit dapat dijadikan fotokatalis dalam proses fotodegradasi dalam menangani limbah zat warna batik cual.